2012
DOI: 10.1093/trstmh/trs017
|View full text |Cite
|
Sign up to set email alerts
|

Red blood cell disorders in recently arrived African immigrants to Gran Canaria, Spain

Abstract: These results suggest that, even in the presence of normal Hb and MCV values, including haemoglobinopathies in the initial screening of newly arrived sub-Saharan immigrants would be very useful.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 25 publications
0
6
0
1
Order By: Relevance
“…Haematological data of African migrants in Europe largely originate from specific subgroups or recently arrived refugees . To the best of our knowledge, the present haematological data are the first on resident sub‐Saharan Africans in Europe most of whom had migrated more than 10 years ago.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Haematological data of African migrants in Europe largely originate from specific subgroups or recently arrived refugees . To the best of our knowledge, the present haematological data are the first on resident sub‐Saharan Africans in Europe most of whom had migrated more than 10 years ago.…”
Section: Discussionmentioning
confidence: 82%
“…In comparison with African Americans, most individuals of African ancestry in Europe have a lesser degree of Caucasian admixture , a more recent migration history, and thus a lower rate of acculturation. In Europe, the scanty haematological figures on African migrants originate from recently arrived refugees, hospital outpatients or special risk groups including mixed populations . In contrast, no data are available for the large group of permanently resident first‐generation African migrants, and in particular, on the haematological differences between this group and Europeans or African Americans.…”
Section: Introductionmentioning
confidence: 99%
“…Some medical aspects of these immigrants deserve special attention. [20] The immigrant group may have health and cultural characteristics that, if not acknowledged by medical providers, may adversely affect health outcomes. [21] Many health systems worldwide are struggling on the national level to develop structured systems and guidelines to optimize the health delivery to the new arrivals, but currently, there is no consensus about the best approach.…”
Section: Discussionmentioning
confidence: 99%
“…We recruited people who were temporarily lodged in shelters as part of the general screening for imported diseases. Physical examination and supplementary face-to-face interview in English or French following a pre-established questionnaire (de-la-Iglesia-Inigo et al, 2013;Sanz-Pelaez et al, 2008) was done as previously reported . Blood samples were obtained from all of the participants.…”
Section: Study Populationmentioning
confidence: 99%